XMEGA-Based Implementation of Four-Switch, Three-Phase Voltage Source Inverter-Fed Induction Motor Drive - Ehsan Boloor Kashani; Abolfazl Halavei Niasar (Institute of Advanced Engineering and Science, 2013)
Induction motors offer many advantages tools, and therefore are becoming very popular industrially and commercially. This paper presents the implementation of Xmega microcontroller based PWM inverter controlled of four-switch three phase voltage source inverter (FSTPI) fed induction motor drive. The reduction of the number of power switches from six to four improves the cost effectiveness, volume-compactness and reliability of the three phase inverters in addition to less complexity of control algorithms and reduced interface circuits. Simulation and experimental work are carried out and results presented to demonstrate the feasibility of the proposed approach. Simulation is carried out using SIMULINK and in experimental work, a prototype model is built to verify the simulation results. XMEGA microcontroller (XMEGA64A3) is used to generate the PWM pulses with a new algorithm for FSTPI to drive a 5 hp, 3-phase induction motor. Experimental and simulation results show that the proposed drive system provides a fast speed response and good disturbance rejection capability.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.2533